Peranan Mahasiswa KKNT dalam Melaksanakan Program Kerja Tambahan di Lokasi Pengabdian Desa Grujugan - Putra, Fahrizal Ananda; Setyawan, Agung; Citrawati, Tyasmiarni; Astuti, Rahayu Fuji (BEKTI : Jurnal Pengabdian kepada Masyarakat, 2024)
The Community Service Program (KKNT) is a form of student engagement aimed at contributing to rural development. This study aims to analyze the role of KKNT students in implementing additional work programs in Grujugan Village. A qualitative approach was used, with data collected through interviews, observations, and documentation. The findings indicate that KKNT students play a crucial role in various aspects, including local potential development, community empowerment, and improving educational quality. The additional work programs, such as skills training, educational activities, and health outreach, successfully attracted active community participation and increased awareness of the importance of collaboration in village development. Thus, the role of KKNT students extends beyond academic aspects, emphasizing social relationship building and sustainable community development.